Oats in healthy gluten-free and regular diets: A perspective. (August 2018) - Smulders, Marinus J.M.; van de Wiel, Clemens C.M.; van den Broeck, Hetty C.; van der Meer, Ingrid M.; Israel-Hoevelaken, T.P.M.; Timmer, Ruud D.; van Dinter, Bert-Jan; Braun, Susanne; Gilissen, Luud J.W.J.
Abstract: During the 20th century, the economic position of oats ( Avena sativa L.) decreased strongly in favour of higher yielding crops including winter wheat and maize. Presently, oat represents only ~ 1.3% of the total world grain production, and its production system is fragmented. Nonetheless, current interest is growing because of recent knowledge on its potential benefits in food, feed and agriculture. This perspective will serve as a further impetus, with special focus on the recently valued advantages of oats in human food and health. Five approved European Food Safety Authority (EFSA) health claims apply to oats. Four relate to the oat-specific soluble fibres, the beta-glucans, and concern the maintenance and reduction of blood cholesterol, better blood glucose balance and increased faecal bulk. The fifth claim concerns the high content of unsaturated fatty acids, especially present in the endosperm, which reduces the risks of heart and vascular diseases. Furthermore, oat starch has a low glycemic index, which is favourable for weight control. Oat-specific polyphenols and avenanthramides have antioxidant and anti-inflammatory properties. Thus, oats can contribute significantly to the presently recommended whole-grain diet. Next to globulins, oats contain a small fraction of prolamin storage proteins, called 'avenins', but at a much lower quantity than gluten proteins in wheat, barley and rye. Oat avenins do not contain any of the known coeliac disease epitopes from gluten of wheat, barley and rye. Long-term food studies confirm the safety of oats for coeliac disease patients and the positive health effects of oat products in a gluten-free diet. These effects are general and independent of oat varieties. In the EU (since 2009), the USA (since 2013) and Canada (since 2015) oat products may be sold as gluten-free provided that any gluten contamination level is below 20 ppm. Oats are, however, generally not gluten-free when produced in a conventional production chain, because of regular contamination with wheat, barley or rye. Therefore, establishing a separate gluten-free oat production chain requires controlling all steps in the chain; the strict conditions will be discussed. Genomic tools, including a single nucleotide polymorphism (SNP) marker array and a dense genetic map, have recently been developed and will support marker-assisted breeding. In 2015, the Oat Global initiative emerged enabling a world-wide cooperation starting with a data sharing facility on genotypic, metabolic and phenotypic characteristics. Further, the EU project TRAFOON (Traditional Food Networks) facilitated the transfer of knowledge to small- and medium-sized enterprises (SMEs) to stimulate innovations in oat production, processing, products and marketing, among others with regard to gluten-free. Finally, with focus on counteracting market fragmentation of the global oat market and production chains, interactive innovation strategies between customers (consumers) and companies through co-creation are discussed. Graphical abstract: Logo and Gluten-free oat products from a controlled gluten-free production chain in The Netherlands. Oat consumption has various health benefits for people with coeliac disease and for the general public, but it requires a separate chain to remain gluten-free, and it needs product development. Image 1 Highlights: Five approved EFSA health claims apply to oats. Long-term food studies confirm the safety of oats for coeliac disease patients. Oat products may be sold as gluten-free in the EU and the USA. A separate gluten-free oat production chain is required to avoid contamination. The Oat Global initiative aims to strengthen oat through worldwide cooperation.